(untitled) (Asian Education Studies, 2022)
Use of authentic literature is nothing new to English language classrooms. Teachers who wish to diversify their material and create more engagement with English content have turned to literature as a means to meet this goal. However, fairy tales have often been ignored due to prejudices that either teachers or students have based on modern adaptations of fairy tale content. This paper aims to present the benefits of incorporating fairy tales into English as a Foreign Language (EFL) classrooms by showing their value in a cultural and linguistic context. The article reports the overall gains found in using authentic literature in English courses, narrowing in scope to concentrate on fairy tales in particular. After giving a broad description of how fairy tale conventions increase engagement and understanding in English classes, a deeper look into the cultural and linguistic features is added. It is hoped that teachers looking for more options in material selection will find this article useful for justification in using fairy tales in EFL classrooms.